The Impact of Implementing a Coal Mining Company's CSR Program on The Achievement of Sustainable Livelihood - Nurul Yakin; Gesta Lionanda; Maria Ariesta Utha; Kurniawati Kurniawati (Journal of Social Research, 2023)
This research aims to determine the implementation of the CSR program at coal mining companies at PT X and PT Y and its impact on sustainable livelihoods. This research uses qualitative methods to produce data and information that is reliable and valid. Data collection techniques use observation and discussion. Primary data sources are informants from the company, government, and community as well as secondary data in the form of social mapping results and sustainability reports from PT X and PT Y. The results of this research show that the implementation of CSR programs carried out by PT SustainableLifee for communities living around operational areas includes the dimensions of social capital, human capital, natural capital, physical capital, and financial capital so that communities not only have power but also have independence from all aspects of life.